The Effect of Promotion Servicescape, Destination Image Visiting The Thousand Island of DKI Jakarta - Trihandayani, Estiningsih; Limakrisna, Nandan; Muharram, Hari (Riviera Publishing, 2022)
Introduction: Tourism is one of the government's priority efforts to improve the Indonesian economy. that tourism or what is often referred to as a tourist place is a geographical area that is in one or more administrative areas where the tourist place is located. Public space, tourism services, accessibility and a sense of togetherness are interconnected and complement the realization of tourism. If the offer of the destination is attractive, it will definitely encourage visitors to visit the tourist attraction. Because tourism potential is a factor that causes visitors to visit a tourist spot. If the visitors feel satisfaction (satisfaction) with the tourist attractions, they will definitely return to the tourist attractions (revisit intention) and will then provide recommendations (intention to recommend) to others. Method: This study uses SEM (Structural Equation Modeling) using SPSS software version 22 and LISREL SEM software. The research was conducted in the Thousand Islands , DKI Jakarta. From the research conducted, the independent variable has a significant effect on the dependent variable. Result: Based on the results of the study, the Destination Image variable has a significant influence to Revisit Intention through Perceived Value. This shows that, the more the image produced, the better the satisfaction and stimulation obtained visitor's intention to return. Conclusion: all hypotheses in the study can be accepted.